Modelo De Gestión: Una Alternativa De Cambio Para La Producción Y Comercialización.Estudio De Caso: Mora En La Parroquia El Altar, Ecuador - Romero, Gabriela Natalí Fonseca; Vizuete, Danny Daniel Castillo; Yépez, Carlos Benjamín Ricaurte; Báez, Luis Alberto Quevedo (European Scientific Journal, ESJ, 2017)
In Ecuador, agriculture has an important role to play in its economic development. This, however, is closely related to the change in the production system and consequently its production chains. This fact has made agriculture one of the main sources of income for rural populations in the country. The Altar is a rural parish of Ecuador which belongs to the Penipe canton of the province of Chimborazo due to its geographical location. It has several climates that facilitate the development of agriculture, and a big part of its population is dedicated to the cultivation of Blackberry. Thus, based on the current territorial model, created from a production approach, a proposal for a management model was designed. This proposal aims to improve agricultural production, generate added value, and introduce new agricultural products into the Markets for marketing. In conclusion, the proposed management model is a tool that can be applied to the producers and marketers of the Altar parish, with the purpose of generating greater economic income.